AN ANALYSIS OF THE DETERMINANTS OF PADDY AND PULSE DEVELOPMENT IN PAPUA PROVINCE - Demas Wamaerand; Kuntoro Boga Andri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
This study aims to: (1) mapping the distribution pattern of the application of agricultural technology innovation specific locations, (2) determine the critical success factors  distribution  application  of  agricultural  technology  innovation  specific locations,  (3)  improvement  of  distribution  patterns  and  acceleration  of  the  adoption and diffusion of technological innovations to support agribusiness and agroindustrial rice, sweet potatoes and  soybeans in Papua. The research activities carried out during March  2011  to  February  2014  using  three  approaches  (methods),  namely  (1)  Desk Study  on  the  SL-  PTT  rice,  soybean  and  sweet  potato  (2)  surveys  to  obtain quantitative  data in  three  districts  purposively  selected  with  10-  20  respondents, (3) the application pattern of diffusion through the demonstration of quality seeds of rice, corn  and  soybeans  in  the  BPP  or  a  farmer  seed  sources  in  three  selected  districts.Agronomic  data  were tabulated  and  analyzed  descriptively.  Analysis  of  the level  of efficiency  in  the  application  of  technology  used  indicator  plots  the  balance  receiptsand  fees  or  analysis  of  R  /  C  ratio.  To  measure  the  success  of  the  application  of technological  innovations  in  the  plots  need  to  set  performance  indicators,  covering aspects of the use of inputs, processes, outputs, outcomes, benefits and impacts. The results show that the dissemination of technological innovations for the development of location-specific agricultural commodities  of rice, corn, soybean and sweet potato, has  spread  in  most  regions  crop  farming  development  centers  in  Papua.  But  only concentrated  around  the  transmigration  settlement  area.  New  varieties  of  soybean plants  yielding  seeds  and  rice  showed  better  productivity  than  the  old  varieties  that have  been  repeatedly  planted  by  farmers.  Yielding  varieties  of  maize  is  being introduced less developed because it is still constrained by marketing, if the market is readily available, farmers are willing to develop it.